Reinventing ecolabels in the era of augmented reality: An experimental study on the case of fair-trade coffee - Dekhili, Sihem; Ertz, Myriam (Journal of cleaner production, 2024)
This research is interested in the effect of augmented reality (AR) technology on ecolabels’ effectiveness. Based on a conceptual model, including control variables, the authors tested the effect of augmented and enriched information on evaluating messages around ecolabels and purchase intention for eco-labeled products. A between-subject experiment on fair-trade coffee involving 264 Canadian consumers was conducted. The experimental plan includes five cells: 2 (augmented reality: absence vs. presence) × 2 (information richness: low vs. high) + 1 control group (absence of ecolabel). The results confirm that AR and enriched information significantly increase the perceived quality and credibility of information around ecolabels, as well as purchase intention for eco-labeled products. Moreover, a significant interaction effect between the medium and the level of information detail was noted for purchase intention. This effect is influenced by the perceived novelty and coolness of the packaging, the degree of the perceived complexity of AR, the level of consumer involvement with the product, and income.